Pengembangan Video Pembelajaran Perawatan Kendaraan Ringan Bermuatan Nilai Karakter Untuk Siswa SMK - Edi Elisa; Dr. Kadek Rihendra Dantes; Gede Arya Agung Prasmanta Yoga (UNIVERSITAS PENDIDIKAN GANESHA, 2023)
Abstract This study aims to develop a light vehicle maintenance learning video containing character values, and to test the feasibility and practicality of the learning video. This research belongs to the type of Research and Development (R&D) research with the Hannafin and Peck development model. The instruments used in data collection were questionnaires for material experts, media experts, and field trials. (a) The research script in the field trial is the students of SMK Negeri 3 Singaraja. The feasibility level is obtained based on the assessment of media experts, material experts, with a percentage with a percentage value of (1) Material experts getting a score of 96.5%, (2) Media experts with a percentage value of 89.16%. The level of practicality can be based on small group trials and large group trials, with a percentage value of (1) Small group trials obtaining a value of 84.5%, (2) large group trials obtaining a percentage value of 86.93%. Based on these results, it can be stated that this media is very feasible in terms of material, and media, as well as practical to use based on responses from respondents, so that this media can be used as a learning medium for light vehicle maintenance that is suitable for use as a learning medium. Keywords : Learning Media, Video, Light Vehicle Maintenance, Character Value.